The Role of Self-Esteem in Predicting Parent-Child Relationships and Students' Emotion Regulation: A Structural Equation Modeling Approach - Muntamah, Bening Siti; Wulandari, Primatia Yogi; Suminar, Dewi Retno; Pratama, Muhammad Fikri; Ulwiyyyah (Psympathic : Jurnal Ilmiah Psikologi, 2025)
Adolescents with risky behaviors often struggle to regulate their emotions adaptively. Emotion regulation is essential for helping adolescents evaluate and respond to emotional situations in a healthy manner. Parent-child relationships and self-esteem have been found to influence these regulation abilities. This study aimed to examine whether self-esteem mediates the relationship between adolescents’ perceptions of parent-child relationships and their use of emotion regulation strategies. This quantitative research involved 214 junior high school students identified with tendencies toward risky behavior, using a cross-sectional design and convenience sampling. Data were analyzed using Structural Equation Modeling (SEM) with IBM AMOS 24. The results showed that self-esteem partially and fully mediated the relationship between parent-child relationships and emotion regulation strategies, including Cognitive Reappraisal and Expressive Suppression. These findings highlight the significance of enhancing family-based interventions and fostering adolescent self-esteem to support effective emotion regulation, particularly for those at risk of maladaptive behavior.